2008
DOI: 10.1016/j.fuel.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of BaCO3 addition on the sintering behavior of lignite coal fly ash

Abstract: The effect of BaCO 3 (witherite) addition on the sintering behavior of lignite coal fly ash taken from the Seyitömer power plant of Kütahya/Turkey was examined at temperatures of 1100, 1150 and 1200°C in air atmosphere. Bloating of the fly ash samples sintered at 1150°C was prevented, that is, the decomposition temperature of CaSO 4 in the fly ash is shifted to a higher temperature, and their physicomechanical properties (porosity, water absorption, bulk density and bending strength) were improved with BaCO 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Although bodies with SFA had lower strength and higher absorption, they showed higher shrinkage compared to those with TFA due to the presence of higher amounts of fluxing materials such as alkaline and alkaline–earth elements (K 2 O, Na 2 O, Fe 2 O 3 , MgO, and CaO). As the content increased further, the specimens swelled resulting from the evolved gases during the thermal decomposition reactions which is also detected in other researches (Ersoy et al, 2008; Kockal and Ozturan, 2011). The results indicated that the water absorption of bodies increased due to increase in the amount of fly ash.…”
Section: Resultssupporting
confidence: 75%
“…Although bodies with SFA had lower strength and higher absorption, they showed higher shrinkage compared to those with TFA due to the presence of higher amounts of fluxing materials such as alkaline and alkaline–earth elements (K 2 O, Na 2 O, Fe 2 O 3 , MgO, and CaO). As the content increased further, the specimens swelled resulting from the evolved gases during the thermal decomposition reactions which is also detected in other researches (Ersoy et al, 2008; Kockal and Ozturan, 2011). The results indicated that the water absorption of bodies increased due to increase in the amount of fly ash.…”
Section: Resultssupporting
confidence: 75%
“…It is well-known (35) that some of the impurities contained in the FA, such as alkaline metal oxides (Na 2 O and K 2 O), alkaline-earth metal oxides (CaO and MgO), and iron oxides, can act as fluxes that promote the formation of a great deal of liquid in the materials at high temperatures. The presence of large proportions of BaCO 3 and SrCO 3 increased even more the fluxing effect on the FA and on other components of the precursor mixtures (36,37), especially in the case of composition 1. Furthermore, the diffusion of BaO and SrO into the structure of the aluminosilicates present in the FA could lead to the formation of additional amounts of amorphous phases (38), which in turn could be easily melted at high temperatures, especially in the presence of a large amount of fluxing agents.…”
Section: Hexacelsian To Celsian Conversion Fraction (F)mentioning
confidence: 99%
“…The formation of soluble sulfates is caused by the reaction between the available SO x and free Na 2 O, K 2 O, CaO, the later coming from the decomposition of lime, which originates soluble calcium sulfates, mainly in the mineral phase of gypsum [153] or anhydrite [154]. If soluble sulfates are already present in the unfired wet blend, dry efflorescence can be avoided by adding some BaCO 3 , as insoluble BaSO 4 is formed [155].…”
Section: Building Ceramicsmentioning
confidence: 99%